Persepsi Guru Bimbingan dan Konseling terhadap Pendidikan Karakter Siswa di SMA Negeri 1 Panti - Asnita, Riza; Syawaluddin, Syawaluddin (Al-DYAS, 2023)
Character education, it is really needed not only at school but also at home and in society. Now it is no longer the character of education participants for early childhood to adolescence, but also adults. Absolutely necessary for the survival of this nation, the competition imagines what will happen in the following yaers if character education is not applied in life. At some point the children will face competition with peers from various countries around the world. Character education will be very important for our lives, if there is no character education, students will be disorganized, no manners, and no manners.